(untitled) (Research, Society and Development, 2023)
Since 2012, a growing visibility of trans men in the media and social movements has been observed in Brazil. But studies on transmasculinities are practically non-existent and trans men seem to have less visibility than female transsexuals. This article aims to analyze studies on transgender people and masculinities in Brazil. This is a narrative review of the literature in Brazilian scientific databases. We identified 10 publications between 2018 and 2021 that were described and analyzed according to identified thematic categories. As a methodological strategy, we outlined an overview of this scientific production. The results demonstrate a diversity in the research areas, as well as in the formation and performance of the authors. Identified themes were discussed: suicidal thoughts; gender dysphoria; performative masculinities; performativity; homo/transphobia and abject body; male transgenderism; transsexualization process and the struggle for depathologization; transsexuality and social media and production of masculinities. Conclusion: The analyzed studies cover a variety of different areas and categories, having as a guiding principle the research on trans people with a focus on male transsexuality. We understand that it is relevant that the theme is inserted in the most diverse areas of research, including health, education, communication and human and applied sciences, which demonstrates the importance and relevance of studies on gender identity.